Effect of the E-Mentoring Process on Youth’s Career Development - Çiğdem Vatansever; Fatma Ceylan (Istanbul Management Journal)
E-mentoring can be defined as an approach that is applied electronically or via the internet to provide personal, useful, specific, synchronized, holistic, accessible, and long-lasting mentoring support to establish a relationship between senior and less experienced individuals. Although studies on e-mentoring are relatively new and few, studies show that it is an effective method of mentorship. The aim of our study is to reveal the effect of this process on the choice of profession and the career development of university students who participate in e-mentoring programs. The research sample consists of young people (age ranges between 14-30) who receive support through an e-mentoring platform established by a nongovernmental organization. The findings show that e-mentoring supports the career development of young people who participate in this process. The mentors are effective in their role as “teachers” with close and sincere communication styles and experiences. The mentors show a guiding attitude to the participants in their career choices and help to eliminate uncertainty by trying to answer the questions in youth’s minds.